2022
DOI: 10.1093/nargab/lqac018
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven identification of inherent features of eukaryotic stress-responsive genes

Abstract: Living organisms are continuously challenged by changes in their environment that can propagate to stresses at the cellular level, such as rapid changes in osmolarity or oxygen tension. To survive these sudden changes, cells have developed stress-responsive mechanisms that tune cellular processes. The response of Saccharomyces cerevisiae to osmostress includes a massive reprogramming of gene expression. Identifying the inherent features of stress-responsive genes is of significant interest for understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Similarly, Lehner et al used the normalized sum of squares of log2- expression changes to infer gene-level transcriptional plasticity from Saccharomyces cerevisiae microarray dataset 5 . These studies found that certain genetic traits, such as promoter architecture, nucleosome organization, and histone modification patterns, may significantly influence eukaryotic gene transcriptional plasticity 6 10 . While the transcriptional machinery and the nucleoid organization of prokaryotic organisms fundamentally differ from those of eukaryotes 11 , 12 , a recent investigation into E. coli promoter evolution showed that long-term natural selection favors the retention of high promoter TP despite the presence of segregating mutations 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lehner et al used the normalized sum of squares of log2- expression changes to infer gene-level transcriptional plasticity from Saccharomyces cerevisiae microarray dataset 5 . These studies found that certain genetic traits, such as promoter architecture, nucleosome organization, and histone modification patterns, may significantly influence eukaryotic gene transcriptional plasticity 6 10 . While the transcriptional machinery and the nucleoid organization of prokaryotic organisms fundamentally differ from those of eukaryotes 11 , 12 , a recent investigation into E. coli promoter evolution showed that long-term natural selection favors the retention of high promoter TP despite the presence of segregating mutations 2 .…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae microarray dataset 5 . These studies found that certain genetic traits, such as promoter architecture, nucleosome organization, and histone modification patterns may significantly influence eukaryotic gene transcriptional plasticity [6][7][8][9][10] . While the transcriptional machinery and the nucleoid organization of prokaryotic organisms fundamentally differ from those of eukaryotes 11,12 , a recent investigation into E. coli promoter evolution showed that long-term natural selection favors the retention of high promoter TP despite the presence of segregating mutations 2 .…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae microarray dataset 5 . These studies found that certain genetic traits, such as promoter architecture, nucleosome organization, and histone modification patterns may significantly influence eukaryotic gene transcriptional plasticity [6][7][8][9][10] . While the transcriptional machinery and the nucleoid organization of prokaryotic organisms fundamentally differ from those of eukaryotes 11,12 , a recent investigation into E. coli promoter evolution showed that long-term natural selection favors the retention of high promoter TP despite the presence of segregating mutations 2 .…”
Section: Introductionmentioning
confidence: 99%